BUDAYA MAHASISWA DALAM MENGGUNAKAN PIRATED BOOKS DI PERGURUAN TINGGI KOTA PEKANBARU - Ismail Ismail; Alfiah Alfiah; Darni Darni (POTENSIA: Jurnal Kependidikan Islam, 2018)
This study aimed to know the culture of students in using pirated books. The location of the study was conducted at State Islamic University of Sultan Syarif Kasim Riau), University of Riau, Universitas Islam Riau, and Lancang Kuning University in Pekanbaru City. Based on the analysis of student economic factors, it shows that the student culture in using pirated books was not because of economic factors. It was evidenced by most of the students with good economic conditions or in the middle to lower class. Based on students' understanding of Copyright, it indicated that students comprehend and understand about copyright. However, respondents considered the copy of the book for the benefit of education does not violate the copyright because to facilitate the science. Actually a photocopy of a book for the benefit of education to facilitate the demand for science is basically an act of copyright infringement because it includes actions to reproduce without permission and disseminate it. Student’s attitudes to regular ordinary photocopies/copies are familiar with copier/pirate books. Based on the habits (culture) of students in buying reference books where the purchase of photocopy reference books/pirates is already a student habit.